Advances in National Brand and Private Label Marketing: Second International Conference, 2015 - Martínez-López, Francisco J (Springer, 2015)
This book presents the latest research and recent studies in the field of national brand and private label marketing. It covers a wide range of topics, including retailing, marketing, general business, psychology, economics and statistics. It addresses diverse areas of application, such as brand naming and packaging decisions, price elasticity, positioning, branding, consumer motivation, online communities, economic crisis, strategies in growth and mature private labels. The contributions are organized according to the following themes: consumer behaviour, strategic decisions, branding, market trends and theoretical research. The book presents a collection of original, rigorous and relevant contributions from the 2015 National Brands and Private Label Marketing conference in Barcelona.